2022
DOI: 10.3389/fmed.2022.1037408
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of B cells in lupus erythematosus skin biopsies in the context of different immune cell infiltration patterns

Abstract: Cutaneous lesions in lupus erythematosus (LE) subtypes are heterogenous. In line with the heterogeneity of the clinical presentation, the underlying lesional inflammation in LE skin samples is defined by different immune cell infiltrates. Pathophysiologically, lesional inflammation is driven by autoreactive cytotoxic T cells, targeting keratinocytes; plasmacytoid dendritic cells (pDCs), producing large amounts of interferon (IFN); and B cells, whose function in cutaneous LE is still unclear. This study aims to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…PDC infiltrates are observed in a great proportion of skin biopsies and can form clusters in CLE skin lesions [ 38 , 40 ]; however, not all skin lesions harbor a pDC infiltrate [ 41 ]. Recently, single-cell ribonucleic acid (RNA) and spatial RNA sequencing has shown that even healthy-appearing skin of CLE patients contains a type I IFN-rich environment and that CD16+ DCs undergo IFN priming in the skin, leading to proinflammatory subtypes [ 42 ].…”
Section: Pathogenesismentioning
confidence: 99%
See 4 more Smart Citations
“…PDC infiltrates are observed in a great proportion of skin biopsies and can form clusters in CLE skin lesions [ 38 , 40 ]; however, not all skin lesions harbor a pDC infiltrate [ 41 ]. Recently, single-cell ribonucleic acid (RNA) and spatial RNA sequencing has shown that even healthy-appearing skin of CLE patients contains a type I IFN-rich environment and that CD16+ DCs undergo IFN priming in the skin, leading to proinflammatory subtypes [ 42 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…Recently, the understanding of the pathophysiological role of B cells in LE has shifted, since strong B-cell signatures and lesional B-cell infiltrates have been described in patients with autoantibody-negative CLE [ 41 , 78 ]. Beside antibody production, B cells can contribute to the autoimmune reaction by different mechanisms.…”
Section: Pathogenesismentioning
confidence: 99%
See 3 more Smart Citations